Low-temperature cohesive and adhesive strength testing of contact surface between bitumen and mineral aggregates by image analysis. (20th September 2018) - Xu, Yazhi; Zheng, Chuanfeng; Feng, Yupeng; Guo, Xuedong
Highlights: Test technology of asphalt cohesive and adhesive strengths was investigated. Image analysis was employed to identify the cohesive and adhesive failure areas. Least-squares method was adopted to address the discreteness of the data. Abstract: The quantitative test technology of asphalt cohesive and adhesive strengths was investigated. An accurate force measuring device was used to perform a destructive test. The cohesive and adhesive strengths of bitumen were determined according to the relationship among tensile failure load, failure area, and strength. Image processing technology was employed to accurately identify the cohesive and adhesive failure areas. Least-squares method was adopted to address the discreteness of the data. Results show that this quantitative testing technology can be used to accurately determine the cohesive and adhesive strengths of the contact surface between bitumen and mineral aggregates under different low-temperature conditions. The proposed quantitative testing technology provides an experimental basis for future work.